THE EXISTENCE OF RENCONG MAKING AS A CULTURAL PRODUCT IN ACEH: A STUDY IN BAET RAYA DISTRICT ACEH BESAR REGENCY - Rika Andalya Bukhari; Bustami Abubakar; Asmanidar (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
This article is entitled